2014
DOI: 10.1155/2014/179040
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis for Finding Serum Markers of Ovarian Cancer

Abstract: A combination of peptide ligand library beads (PLLB) and 1D gel liquid chromatography-mass spectrometry/mass spectrometry (1DGel-LC-MS/MS) was employed to analyze serum samples from patients with ovarian cancer and from healthy controls. Proteomic analysis identified 1200 serum proteins, among which 57 proteins were upregulated and 10 were downregulated in the sera from cancer patients. Retinol binding protein 4 (RBP4) is highly upregulated in the ovarian cancer serum samples. ELISA was employed to measure pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Several studies have showed that RBP4 has a role in some types of cancers such as lung[35], pancreatic[36], ovarian[25], squamous cell[26], colorectal[24], prostate cancer[23] and hepatocellular carcinoma[27]. For example, Hisanori Uehara et al[23] showed that RBP4 expression is increased in prostate cancer cells and associated with prostate cancer cell growth in vitro study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have showed that RBP4 has a role in some types of cancers such as lung[35], pancreatic[36], ovarian[25], squamous cell[26], colorectal[24], prostate cancer[23] and hepatocellular carcinoma[27]. For example, Hisanori Uehara et al[23] showed that RBP4 expression is increased in prostate cancer cells and associated with prostate cancer cell growth in vitro study.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al observed the over expression of RBP4 protein in HCC cell lines compared to normal livers (P < 0.001), which correlated with metastatic potential[27]. In addition, Cheng et al[25] indicated RBP4 expression levels in normal ovarian tissue and plasma of healthy individuals were lower than those in ovarian cancer tissues and plasma of ovarian cancer patients. Moreover, Patz et al [35] and Chen et al[26] suggested RBP4 might be used as a biomarker for the diagnosis of lung cancer and oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Fei et al reported lower RBP4 serum levels in patients with colon cancer than in healthy individuals [17]; on the other hand, Karunanithi et al and Abola et alhave shown that elevated RBP4 is associated with colon cancer progression and liver metastasis [18,19]. There are also studies showing the importance of this protein in ovarian, renal, hepatocellular, oral squamous cell, and pancreatic cancer patients [20][21][22][23][24]. Such analyses conducted in patients with breast cancer suggested a link between elevated RBP4 and the risk of breast cancer [25].…”
mentioning
confidence: 99%
“…Proteomic analyses identified 1200 serum proteins, among which 57 were upregulated in the sera collected from cancer patients. Retinol binding protein 4 (RBP4), which is an adipokine secreted by adipose tissue and liver, was found to be highly elevated in sera of OvCa patients compared to healthy individuals [21]. These examples suggest that proteomics profiles of OvCa patients’ sera are distinct from those of sera of healthy controls.…”
Section: Emerging Serum Biomarkersmentioning
confidence: 99%